The Effect of the Combination of Marmet-Oketani Massage Technique and Soybean Consumption (Glycin max) on Breast Milk (ASI) in Post Partum Mothers at the Siswani Lubuk Pakam Maternity Clinic - Damayanti; Romauli Anna Teresia Marbun; Annisa Maharani; Yuri (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Breast milk (ASI) is a healthy and perfect foods for babies, containing all the nutrients needed for optimal growth and development by babies. Insufficient breast milk is a threat to children's growth and development, which will ultimately affect their health. The Marmet-Oketani massage technique will synergistically increase the flexibility of the breasts and nipples to become softer. The combination with soybeans will stimulate the production of breast milk itself so that the baby's needs for nutrients are fulfilled. Goal of the research is to effect the combination of Marmet-Oketani massage technique as well as soybean consumption (Glycin max) on breast milk (ASI) in Post Partum Mothers at the Siswani Lubuk Pakam Maternity Clinic. The study was conducted on 54 postpartum mothers with purposive sampling techniques with pre-experimental method methods with the design of The One Group Pretest Posttest Design. Breast milk production in the treatment group (given marmet-oketani technique) with many categories amounted to 89.47% (17 respondents), smooth milk production in the control group (given marmet-oketani technique) and soybean consumption with many categories of 18 (94.73%). Based on the results of Chi-Square statistical test analysis, a p-value of 0.025 < ? 0.05 was obtained, this shows that there is an influence of the provision of marmet-oketani techniques and soybean consumption with postpartum maternal milk production at the Siswanti Lubuk Pakam Midwife Clinic. It is recommended that future researchers conduct research on other massage techniques to obtain quality breast milk